A virtual learning environment readiness in Universiti Teknologi Malaysia (UTM) - Ahmed, Abdirahman Abdulahi (2013)
Many factors influence teaching nowadays, some universities in the worldwide offer web-based courses distributed by virtual learning environment. A virtual learning environment (VLE), which is an electronic system, provides various kinds of online interactions between students and lecturers, including online learning and assessment. Up till now, there are still many universities that did not fully establish a VLE in their educational institutions. This study investigates the students' point of view towards VLE readiness in Universiti Teknologi Malaysia (UTM), and presents an evaluation of VLE implementation in UTM. Data were collected from the questionnaire which completed by 140 UTM students. The questionnaire was developed based on Technology Readiness Index (TRI) Model by Parasuraman (2000). This study argues that the TRI is the most suitable model for this research. This study findings show that the VLE is ready to be applied in Universiti Teknologi Malaysia. Some of the VLE have been implementing in UTM context such as Moodle for its e-learning system. To sum up, this study shows that VLE implementation leads to better leaning performance